Controls of carbon turnover in tropical peatlands - Hoyos Santillán, Jorge (2014)
Lowland tropical peatlands can act as sinks and sources of carbon, interchanging greenhouse gases (GHG) with the atmosphere. Despite the importance of lowland tropical peatlands in the past, present and future global carbon cycle, uncertainties exists about the controls regulating the processes of carbon turnover. Therefore, this study examined different controls of carbon turnover, including abiotic, biotic and anthropogenic. For this purpose, six peatlands with different dominant vegetation were selected in the north western region of the Republic of Panama (9° 4' 16.06" N; 82° 6' 28.98" W). Two phasic communities were used as experimental models; Raphia taedigera palm swamps and mixed forest swamps with Campnosperma panamensis. A combination of in situ and ex situ experiments were performed between March 2010 and November 2012: i) ex situ respirometric assays were used to quantify differences in carbon turnover through the peat profile under different redox regimes, ii) litter bags experiments were used to investigate the effect of plant materials with distinct botanical origins on peat accumulation, iii) the effect of vegetation on greenhouse gases emissions was assessed with in situ and ex situ experiments and iv) land use change (LUC) was monitored to evaluate its consequences on the short term carbon turnover processes. Ex situ respirometric assays suggested that organic matter composition of peat plays a major role in controlling the potential CO2 and CH4 production. Under anaerobic conditions, the potential CO2 and CH4 production decreased with depth. The potential CO2 and CH4 productions in the surface peat layers of the anaerobic assays were 7 and 120 fold higher than those in deeper layers of the peat profile respectively. The change in redox regime affected the carbon turnover; the CO2 potential production in the surface layers (< 50 cm depth) increased 20 fold when exposed to aerobic conditions, whilst the deeper layers (> 50 cm depth) increased 47 fold. In contrast, CH4 production was reduced two orders of magnitude under aerobic conditions. Tissue types of R. taedigera and C. panamensis showed different in situ decomposition rates. Decomposition was significantly slower belowground than at the surface, reflecting the importance of the redox regime on the litter decomposition. Roots presented the lowest in situ decomposition rates among tissues both at the surface (R. taedigera: 0.59 ± 0.04 y-1; C. panamensis: 0.45 ± 0.01 y-1) and belowground (R. taedigera: 0.13 ± 0.01 y-1; C. panamensis: 0.17 ± 0.005 y-1). Macromolecular analyses revealed that roots and stems have similar composition to the peat material accumulated in deeper layers. Vegetation exerted a direct control on GHG fluxes from lowland tropical peatlands. In both ex situ and in situ measurements, fluxes of CO2 and CH4 varied with vegetation activity. In terms of CO2eq (Addition of mass flow of GHG, converted with the global warming potential of each gas), the agricultural LUC increased CO2eq emissions from the R. taedigera swamp at Cricamola by ca. 20 t CO2eq ha-1 y-1. At the pristine site, CO2, CH4 and N2O contributed with ca. 90, 9 and 1 % of the TCO2eq respectively. In contrast, in the anthropogenically impacted plot, CO2, CH4 and N2O contributed with ca. 29, 69 and 2 % of the TCO2eq respectively. Water table strongly influenced the carbon turnover. Under flooded conditions (water table at or above the surface; 0 to 0.15 m), the CH4 emissions were ca. 4 times higher in comparison with those where the water table was below the surface (−0.01 to −0.4 m). In contrast, CO2 emissions were ca. 1.5 times higher when the water table was below the surface. It was concluded that the interdependence of hydrology, peat composition and vegetation activity are the main factors controlling carbon turnover in the lowland peatlands of the north western region of Panama. This thesis has shown that fine scale alterations of these three factors can have large scale consequences, demonstrating sensitivity to perturbations and ease shift of lowland tropical peatlands from carbon sinks to carbon sources.